Here comes trouble [compact disc, unabridged] : stories from my life - Moore, Michael, 1954 April 23- (Hachette Audio, 2011)
This book is Moore's most personal to date and will be irresistible to fans and foes alike. A sort of anti-memoir, Moore breaks the autobiographical mode while he hilariously presents 20 far-ranging, irreverant vignettes from his own life.